PENINDAKAN DAN PENYELIDIKAN OLEH KANTOR BEA DAN CUKAI TERHADAP PENYELUNDUPAN PAKAIAN BEKAS IMPOR DI KABUPATEN INDRAGIRI HILIR TAHUN 2014-2015 - Rahmat Firdaus; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The background of the problem in this study is Ministerial Regulation No. 51 / M-DAG / PER / 7/2015 clearly regulating the prohibition on the import of used clothing, but in reality, the distribution of imported used clothing is still found in Tembilahan City. The formulation of the problem in this study is how the Enforcement and Investigation by the Madya C Tembilahan Customs and Excise Office on smuggling imported used clothing in Indragiri Hilir district in 2014-2015. This type of research uses a qualitative approach. The purpose of this study was first, to find out about the prosecution and investigation by the Customs and Excise Office of smuggling imported used clothing in Indragiri Hilir district in 2014-2015. Secondly, to find out the findings obtained by the customs and excise office in 2014-2015 and third, to find out the obstacles and evaluation of the Tembilahan Customs and Excise office in conducting prosecution and investigation. The results of this study indicate, even though the C Customs and Excise type office of C Tembilahan has carried out its duties well, by tightening investigations and prosecution, there are still efforts by smugglers to find loopholes to smuggle used clothing into the Tembilahan area. In carrying out its duties in the field of investigation and prosecution of smuggling of imported used clothing, the Customs and Excise office of the C Tembilahan type also has obstacles. Keywords : Prosecution, Customs and Excise Offices, Smuggling of Used Clothing